2018
DOI: 10.1371/journal.pone.0198842
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-binding protein in cervicovaginal fluid as a non-invasive predictor of intra-amniotic infection and impending preterm delivery in women with preterm labor or preterm premature rupture of membranes

Abstract: ObjectiveTo determine whether vitamin D-binding protein (VDBP) in cervicovaginal fluid (CVF) is independently predictive of intra-amniotic infection and imminent spontaneous preterm delivery (SPTD, delivery within 48 hours) in women with preterm labor with intact membranes (PTL) or preterm premature rupture of membranes (PPROM).MethodThis was a single-center retrospective cohort study. CVF samples for VDBP assays were obtained along with serum C-reactive protein (CRP) levels immediately after amniocentesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…A single-centre retrospective cohort study [126] examined VDBP in samples of CVF immediately following amniocentesis collected from women after preterm labour. The study, involving 148 women with preterm labour and 103 with pPROM between 23-34 weeks gestation, found that an increase in concentration of VDBP in CVF independently predicted imminent preterm delivery in women with preterm labour [126].…”
Section: Vdbp and Preterm Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-centre retrospective cohort study [126] examined VDBP in samples of CVF immediately following amniocentesis collected from women after preterm labour. The study, involving 148 women with preterm labour and 103 with pPROM between 23-34 weeks gestation, found that an increase in concentration of VDBP in CVF independently predicted imminent preterm delivery in women with preterm labour [126].…”
Section: Vdbp and Preterm Birthmentioning
confidence: 99%
“…A single-centre retrospective cohort study [126] examined VDBP in samples of CVF immediately following amniocentesis collected from women after preterm labour. The study, involving 148 women with preterm labour and 103 with pPROM between 23-34 weeks gestation, found that an increase in concentration of VDBP in CVF independently predicted imminent preterm delivery in women with preterm labour [126]. Pereira et al [128] also examined 205 proteins in the CVF of 18 women in search of novel non-invasive biomarkers of preterm labour and identified VDBP as being differentially expressed in women who experienced spontaneous preterm birth compared with controls [128].…”
Section: Vdbp and Preterm Birthmentioning
confidence: 99%
“…In accordance with the results of the current study, the previous longitudinal study by Liong et al showed that VDBP is detectable in the CVF of all pregnant women during the second half of pregnancy with no change in the CVF VDBP level between 20 and 35 weeks' gestation [14] suggesting that VDBP is a physiologic constituent of the lower genital tract fluid. In addition, VDBP has been previously identified in the AF of pregnant women [8] and on other experiment to determine the dilution ratio showed that VDBP levels in the AF without intra-amniotic infection were approximately 10 times higher than the levels in the CVF (supplementary materials) [12] . Similarly, the VDBP levels reported in pregnant maternal serum were 1000 times higher than those measured in the CVF in the current study [3] .…”
Section: Discussionmentioning
confidence: 95%
“…The vitamin D metabolites analysed in this study, including VDBP, were not associated with preterm birth or PROM. Preterm birth and PROM have previously been linked to increased levels of VDBP in cervicovaginal fluid (CVF) [56], with a study by Liong et al [57] finding that the VDBP/albumin CVF ratio was a more efficacious and precise biomarker than fetal fibronectin (fFN), the current gold standard, for predicting impending preterm labour. Overall, much of the existing research has explored VDBP levels in CVF, which may explain the discrepancies with our findings since VDBP in this study was measured in plasma/serum.…”
Section: Comparison With Previous Literature and Potential Mechanismsmentioning
confidence: 99%